2009
DOI: 10.1021/jf900097j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Allyl Esters of Fatty Acids and Their Ovicidal Effect on Cydia pomonella (L.)

Abstract: Eight allyl esters of fatty acids were synthesized in moderate to high yields with a novel two-step procedure using glycerol as a starting material. The two-step methodology avoids the use of allyl alcohol. The first step consisted of heating at 80 degrees C for 48 h a 2:1:5 mmol mixture of glycerol, a fatty acid, and chlorotrimethylsilane in a solvent-free medium. The crude compound was then dissolved in butanone and heated at 115 degrees C in the presence of NaI. A tandem Finkelstein rearrangement-eliminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Other authors have described a similar synergism to plant volatiles [21,25]. This could be extremely interesting if confirmed in a field situation.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Other authors have described a similar synergism to plant volatiles [21,25]. This could be extremely interesting if confirmed in a field situation.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, allyl esters can be synthesized from glycerol or fat wastes [21,22], what fosters the re-use of industrial sub products. However, more assays need to be done to fix the proportion of allyl cinnamate into the blend to improve the attractiveness of moths [39,40] and asses it in field conditions, as well as the fate of allyl cinnamate in field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essential oils are mainly mixtures of different compounds, some of which belong to the ester chemical group (Daferera et al, 2000;Skaltsa et al, 2003;Bakkali et al, 2008) that had shown insecticidal properties (Ojimelukwe and Adler, 1999;Peterson et al, 2000;Leelaja et al, 2007;Escribà et al, 2009). Moreover, no adverse effects toward human health or the environment are expected because several of these products are already approved for use as fragrances and food flavors (Bauer et al, 2001;Burdock, 2010).…”
Section: Introductionmentioning
confidence: 99%